Translation - A Civilizational Need - Islam, AZM Qutubul (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v3i0.2685 IIUC STUDIES Vol. - 3, December 2006 (p 185-198)